(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
To evaluate the hearing outcome in canal wall down mastoidectomy with middle ear reconstruction, prospective longitudinal study was done at National Institute of ENT, Dhaka from March 2015 to September 2016. Total 22 patients were included in the study undergoing canal wall down mastoidectomy with 6 months postoperative followup. Hearing outcomes were observed and compared with the preoperative hearing tests. Among the 22 patients 9 (39.1% of subjects) patients had hearing gain, 12 (52.2%) had hearing loss and 1 (4.3%) had no change in hearing postoperatively.Although disease clearance is the main objective in canal wall down mastoidectomy, hearing gain can be achieved if combined with ossiculoplasty and tympanoplasty. The hearing gain or loss depends upon the extension of disease and status of the ossicular chain. Most patients usually experience hearing loss more than the preoperative period due to removal of ossicle or ossicles for the sake of disease clearance. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 195-198